Formação de professores e educação de pessoas com deficiência: concepções de docentes formadores - Almeida, Luisa de Souza Leão (Universidade Federal de São Carlos, 2022)
The development of human resources, specifically the training of secondary teachers, is considered one of the pillars of the inclusive education of disabled students. However, it has been suggested that the undergraduate training received by teachers has not been enough for them to co-create an equity environment for all students. Given this scenario, it is necessary to investigate from what conceptions instructors who train secondary teachers have conducted their training practices. Thus, this study aimed to analyze post-secondary instructors who teach courses on the theme of education of disabled people. Also, we wanted to understand their conceptions about the structuring of disciplines related to this theme and its relationship with the training of future professionals. The research was characterized as a case study conducted at the Universidade Federal do Pará, with the participation of seven instructors from undergraduate courses who teach subjects related to the education of disabled people. Data collection was carried out in two stages: 1) document analysis, referring to the mapping of subjects related to the education of disabled people taught in undergraduate courses on five university campuses; 2) field study, which consisted of conducting semi-structured interviews with university professors. Data analysis was based on the Method of Interpretation of Meanings, which includes three phases: understanding, exploration and interpretative synthesis. The results gave rise to five thematic axes. Axis A, referring to teachers' training and performance paths in the field of Special Education, indicated differences in the following dimensions: a) specific academic training in the area; b) personal, professional or institutional factors and motivations. Axis B, referred to concepts about curriculum and didactics for the education of disabled people. It was identified that, of the 21 undergraduate courses analyzed, 20 had a Libras subject and seven had general subjects in the area of Special Education. Still, in regards to this axis, teachers pointed out that such subjects impact training by sensitizing future teachers and offering initial instruments for their performance. Axis C dealt with institutional aspects and accessibility at the university, indicating a lack of human resources. Axis C results showed the existence of additional training spaces beyond regular training, such as research and extension, especially in Libras. Axis D referred to teachers' conceptions of disability. The results pointed to the perception of individual and institutional barriers present in different relationships with disabled people and the understanding of the need to produce attitudinal changes across disciplines. The organic, social and metaphysical concepts permeated the analyzed discourses. Axis E allowed the knowledge of conceptions about education for disabled people. The results pointed to dimensions such as affection and empathy regarding this process and the importance of legal aspects in the face of perceived resistance. The Specialized Educational Service appeared as the primary reference model for the education of disabled people. The dialogue with the training teachers proved to be decisive in elucidating conceptions and discourses about disabled people, who circulate in different social spaces and impact the training processes.
Teacher training and education of disabled people: conceptions of professors
Keywords: Concepção; Formação inicial; Inclusão escolar; Educação especial; Conception; Initial training; Inclusive education; Special education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::APRENDIZAGEM E DESEMPENHO ACADEMICOS; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::TREINAMENTO DE PESSOAL